2020
DOI: 10.1016/j.yfrne.2020.100860
|View full text |Cite
|
Sign up to set email alerts
|

It takes a neural village: Circuit-based approaches for estrogenic regulation of episodic memory

Abstract: Cognitive behaviors, such as episodic memory formation, are complex processes involving coordinated activity in multiple brain regions. However, much of the research on hormonal regulation of cognition focuses on manipulation of one region at a time or provides a single snapshot of how a systemic treatment affects multiple brain regions without investigating how these regions might interact to mediate hormone effects. Here, we use estrogenic regulation of episodic memory as an example of how circuit-based appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 210 publications
0
3
0
1
Order By: Relevance
“…Loss of endogenous ovarian hormones in gonadectomized female mice also induced dorsal hippocampal atrophy at midlife, but not at young ages, revealing a hormone by age interaction. Even though previous research clearly demonstrated bene cial effects of estrogens on cognitive function and hippocampal synaptic pathology 45 , which cell and receptor within hippocampus is essential for in vivo neuroprotection during midlife in otherwise healthy female mice has remained unclear. Here, we used gonadally intact female mice with selective deletion of ERβ in either astrocytes or neurons to determine if ERβ in either of these cells is essential for neuroprotection at midlife.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of endogenous ovarian hormones in gonadectomized female mice also induced dorsal hippocampal atrophy at midlife, but not at young ages, revealing a hormone by age interaction. Even though previous research clearly demonstrated bene cial effects of estrogens on cognitive function and hippocampal synaptic pathology 45 , which cell and receptor within hippocampus is essential for in vivo neuroprotection during midlife in otherwise healthy female mice has remained unclear. Here, we used gonadally intact female mice with selective deletion of ERβ in either astrocytes or neurons to determine if ERβ in either of these cells is essential for neuroprotection at midlife.…”
Section: Discussionmentioning
confidence: 99%
“…Several estrogen-sensitive regions have been revealed as candidates for mediating the effects of estrogens on body temperature, but evidence suggests that these areas work synergistically, antagonistically, and/or in parallel to modulate whole-body thermoregulation. Whereas estrogens affect body temperature by modulating both heat production and dissipation, many of these effects are mediated specifically or simultaneously via different estrogen-sensitive regions ( 13 ). We recommend a systems-level, circuit-based approach to dissect the distinct thermal effectors modulated by estrogens.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous estrogens are widely circulated and can act at multiple estrogen-sensitive regions and tissues simultaneously. Systemic manipulations of estrogen levels may overlook the interactions between brain regions or tissues and the synergistic or compensatory actions of estrogens ( 13 ). Therefore, dissecting the effects of estrogens on individual cell populations or circuit connections will be necessary for a better understanding of the effects of estrogens on thermoregulation.…”
mentioning
confidence: 99%
“…Implementasi merupakan suatu proses penerapan ide, konsep, kebijakan atau inovasi dalam suatu tindakan praktis sehingga memberikan dampak, baik berupa perubahan pengetahuan, keterampilan maupun nilai dan sikap. (Schwabe, 2020) Aturan adalah perangkat penting dalam segala tindakan dan perbuatan orang. Makin maju dan majemuk suatu masyarakat makin besar peranan aturan dan dapat dikatakan orang tidak dapat hidup dengan layak dan tenang tanpa aturan.…”
Section: Jenis Dataunclassified